AS MUDANÇAS DE COMPORTAMENTO EM PACIENTES COM ALZHEIMER: UM RELATO DE EXPERIÊNCIA - Soares, Jandson de Oliveira; Souza, Maxsuel Oliveira de; Lima, Beatriz Santana de Souza; Cavalcante, Juliana Barbosa Nunes (Gep News, 2017)
Tipo de Apresentação: Pôster